2017
DOI: 10.1016/j.plaphy.2017.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Approaches in modulating proline metabolism in plants for salt and drought stress tolerance: Phytohormones, mineral nutrients and transgenics

Abstract: Major abiotic stress factors such as salt and drought adversely affect important physiological processes and biochemical mechanisms and cause severe loss in crop productivity worldwide. Plants develop various strategies to stand healthy against these stress factors. The accumulation of proline (Pro) is one of the striking metabolic responses of plants to salt and drought stress. Pro biosynthesis and signalling contribute to the redox balance of cell under normal and stressful conditions. However, literature is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
178
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 362 publications
(194 citation statements)
references
References 157 publications
12
178
3
1
Order By: Relevance
“…Another study with 100 sainfoin genotypes from 10 ecotypes showed that drought tolerance was, however, correlated with leaf proline content (Irani et al, 2015). Additionally, there is some indication that it might contribute to upregulation of drought tolerance genes (Szabados and Savouré, 2010;Per et al, 2017). Additionally, there is some indication that it might contribute to upregulation of drought tolerance genes (Szabados and Savouré, 2010;Per et al, 2017).…”
Section: Effects Of Drought On Yield and Condensed Tannin Content In mentioning
confidence: 99%
See 1 more Smart Citation
“…Another study with 100 sainfoin genotypes from 10 ecotypes showed that drought tolerance was, however, correlated with leaf proline content (Irani et al, 2015). Additionally, there is some indication that it might contribute to upregulation of drought tolerance genes (Szabados and Savouré, 2010;Per et al, 2017). Additionally, there is some indication that it might contribute to upregulation of drought tolerance genes (Szabados and Savouré, 2010;Per et al, 2017).…”
Section: Effects Of Drought On Yield and Condensed Tannin Content In mentioning
confidence: 99%
“…This correlation is in accordance with previous studies, and although the cause-and-effect relationship between proline and drought tolerance is not yet fully understood, proline can act as an osmoprotectant, thus stabilizing membranes and maintaining cell turgor. Additionally, there is some indication that it might contribute to upregulation of drought tolerance genes (Szabados and Savouré, 2010;Per et al, 2017). Therefore, the current understanding of CT expression in sainfoin suggests that it should be possible to breed new cultivars with good yields, drought tolerance, and consistent CT profiles, which is important, as farmers need forage legumes with predictable CT traits.…”
Section: Effects Of Drought On Yield and Condensed Tannin Content In mentioning
confidence: 99%
“…Salinity adversely affects important physiological processes and biochemical mechanisms, causes severe loss in crop productivity worldwide (Per et al, 2017) and can cause some biochemical changes in plant cell such as losing of cell turgor and the accumulation of reactive oxygen species (ROS) (Nxele et al, 2017). Reactive oxygen species (ROS) including hydrogen peroxide (H 2 O 2 ), superoxide anions (O 2 •−), hydroxyl radical (OH•) and singlet oxygen ( 1 O 2 ) are by-products of physiological metabolisms, and are precisely controlled by enzymatic and non-enzymatic antioxidant defense systems (You and Chan, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…One of the other cellular responses to saline conditions is the alteration of metabolism and production of compatible solutes (osmolytes) such as proline, which are distributed among different organisms (Mansour and Ali, 2017). The accumulation of proline (Pro) is one of the striking metabolic responses of plants to salt stress (Per et al, 2017). One of the cell parts where stress-related oxidative damage has the most effect is the cell membrane.…”
Section: Introductionmentioning
confidence: 99%
“…However, to adapt to water stress, plants have evolved many acclimation mechanisms, including osmotic adjustment and antioxidant defense systems, which may enhance their ability to grow and develop under drought conditions (Fu and Huang, 2001; Khaleghi et al, 2019). Under water stress conditions, soluble sugars and proline accumulate to serve as osmolytes in various plants, assist in membrane protein stabilization, and ultimately increase plant resistance against water stress (Ashraf and Foolad, 2007; Gomes et al, 2010; Per et al, 2017). Further, ROS scavenging enzymatic antioxidants, such as superoxide dismutase (SOD), peroxidase (POD), catalase (CAT), glutathione reductase (GR), and ascorbate peroxidase (APX) can be activated to clear these excessive ROS (Gill and Tuteja, 2010).…”
Section: Introductionmentioning
confidence: 99%